-7(6)(-1)=

Simple and best practice solution for -7(6)(-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(6)(-1)= equation:


Simplifying
-7(6)(-1) = 0

Multiply -7 * 6
-42 * -1 = 0

Multiply -42 * -1
42 = 0

Solving
42 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 35k=1925 | | 5x-57-2x=63 | | 4x^2-28-32=0 | | 18d^5+6d^4+9d^3= | | 3+4Inx=5 | | -7n-10=60 | | X+9=90 | | 2x+2y+z=11 | | 1-17x+37x=1 | | 19-11/-2 | | 5+2x=-20+5x | | 1/8=z^(6x) | | -14x-25-22=79 | | 14x-25-22=29 | | 18d^5+6d^49+d^3= | | -77=-40m-37m | | 1/3x1/3x1/3x1/3x1/3 | | t-23=78 | | -52+T=4 | | -9(1+7b)=15 | | w+17=19 | | 18x^2-46x-552=0 | | cos(53)=x/7 | | y+50=60 | | 4x+4y=3.5 | | 6y-4=3 | | 9x-3=-33 | | 4m+5n=5 | | 17x+30=-939 | | 2x=6-4x+2-2x | | y=-2E+05ln(x)+1E+06 | | -6--2x/-4 |

Equations solver categories